2020
DOI: 10.1109/twc.2020.2994998
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Link Scheduling in Wireless Networks Under Rayleigh-Fading and Multiuser Interference

Abstract: Link scheduling plays a key role in the network capacity and the transmission delay. In this paper, we study the problem of maximum link scheduling (MLS), aiming to characterize the maximum number of links that can be successfully scheduled simultaneously under Rayleigh-fading and multiuser interference. After analyzing the minimum distance between successful links in the existing GHW scheduling algorithm, we propose a DLS (Distance-based Link Scheduling) algorithm. Then, the global interference is characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Similar assumption was also applied in the previous works (e.g. [3], [5], [6]). However, their works were unsatisfactory to provide a better scheduling performance which refers to scheduling more concurrent links in a single slot for the MLS, and using less slots to schedule all links for the SLS.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar assumption was also applied in the previous works (e.g. [3], [5], [6]). However, their works were unsatisfactory to provide a better scheduling performance which refers to scheduling more concurrent links in a single slot for the MLS, and using less slots to schedule all links for the SLS.…”
Section: Introductionmentioning
confidence: 81%
“…However, the model leads to the design and analysis of link scheduling algorithms more challenging and difficult in return. Consequently, there are few works focusing on link scheduling subject to Rayleigh fading constraint (e.g., [3]- [6]).…”
Section: Introductionmentioning
confidence: 99%
“…The height and the effective height of the vehicle are expressed as and . The velocity of light in free space is represented by c. The Rayleigh fading model is a common model that can represent multipath fading in real-world environments [ 48 , 49 ]. In this work, multipath fading is modeled as Rayleigh fading to represent the LA city environment, which follows the exponential distribution with unit mean.…”
Section: Proposed Ml-based Cell Selection Strategymentioning
confidence: 99%
“…Experimental work conducted in Manhattan [19] found that Rayleigh fading can be a useful model in heavily built-up city centers where there is no line of sight between the transmitter and receiver and many buildings and other objects attenuate, reflect, refract, and diffract the signals. In recent years, the Rayleigh fading model has been considered in numerous research works, such as [20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%